2002
DOI: 10.1111/j.0014-3820.2002.tb01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and the Evolution of Cell-Cycle Durations of Embryos

Abstract: Abstract. Embryos at low risk evolve slower development rates. In seven independent evolutionary contrasts for marine invertebrates (two in asteroids, three in gastropods, one each in phoronids and brachiopods) the more protected embryos had longer cell cycles from first to second cleavage than less protected planktonic embryos. Protected embryos had longer cell cycles even when protected eggs were smaller than planktonic eggs. In an eighth contrast, among tunicates, the embryonic cell cycle was unrelated to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 107 publications
(108 reference statements)
1
32
0
Order By: Relevance
“…The time embryos require to pass from the 2 cell to the 4 cell phase (a cell cycle time) was measured by Strathmann et al (2002) for a range of aquatic organisms (Echinodermata,33 Egg mass (µg C) All data corrected to 15°C using average activation energy value of 0.65 (Gillooly et al 2002), and divided into egg disposition category described in Mollusca, Phoronida, Brachiopoda and Chordata). They observed that embryos at low risk had slower development rates (measured as the time from first to second cleavage of the egg).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The time embryos require to pass from the 2 cell to the 4 cell phase (a cell cycle time) was measured by Strathmann et al (2002) for a range of aquatic organisms (Echinodermata,33 Egg mass (µg C) All data corrected to 15°C using average activation energy value of 0.65 (Gillooly et al 2002), and divided into egg disposition category described in Mollusca, Phoronida, Brachiopoda and Chordata). They observed that embryos at low risk had slower development rates (measured as the time from first to second cleavage of the egg).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that embryos at low risk had slower development rates (measured as the time from first to second cleavage of the egg). Strathmann et al (2002) also considered aggregated and brooded eggs to be less vulnerable. In Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations